2013
DOI: 10.1021/nn400337v
|View full text |Cite
|
Sign up to set email alerts
|

Solution Preparation of Two-Dimensional Covalently Linked Networks by Polymerization of 1,3,5-Tri(4-iodophenyl)benzene on Au(111)

Abstract: The polymerization of 1,3,5-tri(4-iodophenyl)benzene (TIPB) on Au(111) through covalent aryl-aryl coupling is accomplished using a solution-based approach and investigated by scanning tunneling microscopy. Drop-casting of the TIPB monomer onto Au(111) at room temperature results in poorly ordered noncovalent arrangements of molecules and partial dehalogenation. However, drop-casting on a preheated Au(111) substrate yields various topologically distinct covalent aggregates and networks. Interestingly, some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
3
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 37 publications
(67 reference statements)
5
53
3
2
Order By: Relevance
“…The carbon-iodine bond within an organic molecule is known to dissociate upon adsorption on Au, Ag, and Cu surfaces at room temperature as has been shown for various molecules. 15,[36][37][38] This leads in general to a second reaction step, the intermolecular Ullmann carbon-carbon coupling. 15,16,22,36,[39][40][41][42][43][44][45] Here, our initial aim was to utilize an on-surface chemical reaction to produce covalently bonded linear polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The carbon-iodine bond within an organic molecule is known to dissociate upon adsorption on Au, Ag, and Cu surfaces at room temperature as has been shown for various molecules. 15,[36][37][38] This leads in general to a second reaction step, the intermolecular Ullmann carbon-carbon coupling. 15,16,22,36,[39][40][41][42][43][44][45] Here, our initial aim was to utilize an on-surface chemical reaction to produce covalently bonded linear polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The packing differs from that reported in the literature for similar molecules TIPB and TBPB on HOPG. 41,46,49 This is attributed to stronger molecule···substrate interactions due to the presence of the triazine core, which makes TIPT and TBPT stiffer and planar precursors. Varying the solvents revealed that TBPT can form a bicomponent polymorph involving a hexameric R 6 6 (24) hydrogen-bonded arrangement of the solvent (heptanoic acid) molecules.…”
Section: ■ Conclusion and Perspectivesmentioning
confidence: 99%
“…Eder et al showed that increasing molecular concentration can lead to the formation of a nonorganized second monolayer of 1,3,5-tris(4-iodophenyl)benzene molecules on Au(111). 53 Gatti et al observed that solvent molecules can sometimes interact with molecules without an alkyl chain and form a 2D bicomponent structure on Au(111). 54 In this paper the concentration-dependent self-assembly of 1,3,5-tris(4-iodophenyl)benzene molecules at the 1-phenyloctane/graphite interface is investigated.…”
Section: ■ Introductionmentioning
confidence: 99%